MgO NPs catalyzed the synthesis of novel pyridin-3-yl-pyrimidin-2-yl-aminophenyl-amide derivatives and evaluation of pharmacokinetic profiles and biological activity - Gani, Ibtihal Haitham; Al-Obaidi, Zaid (Frontiers in Materials, 2023)
In this study, novel pyridin-3-yl-pyrimidin-2-yl-aminophenyl-amide derivatives using two methods, namely, using trimethylamine as a classical method and using magnesium oxide nanoparticles, were synthesized. Biological activities of the derivatives such as inhibitors of receptor tyrosine kinase, pharmacokinetics profiles, anticancer activity against lung cancer, antibacterial and antifungal activity against specialized aquatic bacterial species, Gram-positive and Gram-negative species, and fungal species, and antioxidant activity were evaluated. The structures of synthetic derivatives were confirmed using FT-IR, 1H-NMR, and 13C-NMR spectra and elemental analysis. The results showed that these compounds possess more cytotoxic activity than the reference drug (i.e., imatinib). Furthermore, compound IIB gives ten-fold lower IC50 values (0.229 μM) than imatinib (2.479 μM) when tested against (A549) lung cancer cell lines employing MTT assay. To investigate antibacterial and antifungal activities, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and minimum fungicidal concentration (MFC) parameters were evaluated, and derivative IIC showed the highest activity (MIC 16–128 μg/mL), which can be attributed to its structure. In addition, the antibacterial and antifungal properties of the derivatives were higher than some drugs. The antioxidant property of the derivatives was studied by using the DPPH (2,2-diphenylpicrylhydrazyl) method, and the results showed that the evaluated IC50 value was close to the IC50 value of ascorbic acid (4.45–4.83 μg/mL).